(untitled) (Journal of Information and Communication Technology, 2016)
One major problem of wireless mesh networks is low throughput and on the other hand, network coding (NC) is a reliable solution to alleviate this problem. In this paper, we evaluate the throughÂput gain of various intersession wireless NC schemes, includÂing signal level (analog) NC and packet level NC, which may include non-duplex flows, over the traditional non-NC schemes in multi-radio, multi-channel and multi-hop networks. We also propose a routing approach in order to increase NC opportuniÂties and evaluate its performance in wireless ad-hoc networks in terms of network throughput.